The Development of A Realistic Mathematics Education (RME)-Based E-Module for Teaching Sequences and Series - Safrina, Khusnul; Mahmuzah, Rifaatul; Munawarah, Nafis (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
It is impossible to separate learning using the RME (Realistic Mathematics Education) approach from the use of learning media. However, the availability of RME-based e-modules in the learning process is still very limited, as teachers continue to rely on printed textbooks for instruction. Therefore, there is a need for more creative and innovative learning media. This study aims to develop and produce a valid and practical RME-based e-module for the topic of sequences and series. This type of research is classified as research and development (R&D) using the ADDIE model (analysis, design, development, implementation, evaluation). The subjects of this study were Grade X students at MAN 4 Aceh Besar. Data collection instruments included questionnaires, interviews, validation sheets, and teacher and student response questionnaires. The research results describe the process and outcomes of developing the e-module, which include the stages of analysis, design, development, implementation, and evaluation.